2006
DOI: 10.1002/eji.200636122
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dendritic cell (FDC)‐FcγRIIB engagement via immune complexes induces the activated FDC phenotype associated with secondary follicle development

Abstract: Follicular dendritic cell (FDC)-FccRIIB levels are up-regulated 1-3 days after challenge of actively immunized mice with Ag. This kinetics suggested that memory cells are not driving this response, prompting the hypothesis that immune complex (IC)-FDC interactions lead to FDC activation. To test this, mice passively immunized with anti-OVA Ab were OVA challenged to produce IC. After 3 days, levels of IC, FccRIIB, ICAM-1, and VCAM-1 on FDC were analyzed. FDC were also stimulated with IC in vitro, and mRNA for F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 45 publications
3
63
0
Order By: Relevance
“…Furthermore, FDCs produce BAFF, and the level of FDC-BAFF produced was enhanced by the addition of OVA ICs (Fig. 6C), and this enhancement was abrogated by the FcR blocker 2.4G2 as previously reported for FDC-ICAM and -VCAM (20). Addition of the decoy-BAFF-R-Fc (Fig.…”
Section: Blockade Of Fdc-fc␥riib -C4bp and -Baff Significantly Inhisupporting
confidence: 78%
“…Furthermore, FDCs produce BAFF, and the level of FDC-BAFF produced was enhanced by the addition of OVA ICs (Fig. 6C), and this enhancement was abrogated by the FcR blocker 2.4G2 as previously reported for FDC-ICAM and -VCAM (20). Addition of the decoy-BAFF-R-Fc (Fig.…”
Section: Blockade Of Fdc-fc␥riib -C4bp and -Baff Significantly Inhisupporting
confidence: 78%
“…Thus, FDCs could be activated and ready to trap ICs and optimally stimulate B cells as soon as the first ICs are made. The ICs themselves can activate FDCs, but that requires 24 -48 h after encountering adequate amounts of ICs (44). The present study indicated that FDCs were activated via TLR4 engagement in 3 days, and that would precede Ab production and IC formation.…”
Section: Discussionmentioning
confidence: 54%
“…Up-regulating these adhesion molecules should promote FDC-B cell interactions, facilitate clustering and presentation of FDC-Ag to B cells, and enhance the GC reaction. The signaling pathway known to up-regulate FDC-ICAM-1 and FDC-VCAM-1 is mediated via the NF-B (43), and up-regulation of FDC-ICAM-1 and FDC-VCAM-1 may be initiated by ICs engaging FDC-Fc␥RIIB (44). Similarly, the NF-B pathway appeared to be activated when FDC-ICAM-1 and FDC-VCAM-1 were up-regulated by LPS, engaging FDC-TLR4 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We first analyzed activation of FDCs in the LNs of mice immunized with PE in the presence or absence of MF59, 7 d after a secondary immunization, checking the expression of CD16/32, a described marker for FDC activation (7,32). The activation of FDCs was generally more evident after immunization with MF59, although it was also observed in the absence of adjuvant (Fig.…”
Section: Upon Immunizations With Mf59 Fdc Activation Is Associated Wmentioning
confidence: 99%
“…Follicular dendritic cells (FDCs) have been described to play a key role in the induction of B cell responses, particularly during reexposure of the immune system to a protein Ag (3)(4)(5)(6). FDCs capture circulating immune complexes (ICs) through the CR2 (CD21/35) and retain them for a long period (up to 3 wk) (3,5,(7)(8)(9). A prolonged exposure of the ICs on the FDC surface facilitates the encounter of the unprocessed Ag with cognate memory B cells (9,10).…”
mentioning
confidence: 99%